Pictures at a revolution : five movies and the birth of the new hollywood - Harris, Mark (Penguin Books, 2014)
The New York Times bestseller that follows the making of five films at a pivotal time in Hollywood history In the mid-1960s, westerns, war movies, and blockbuster musicals like Mary Poppins swept the box office. The Hollywood studio system was astonishingly lucrative for the few who dominated the business. That is, until the tastes of American moviegoers radically- and unexpectedly-changed. By the Oscar ceremonies of 1968, a cultural revolution had hit Hollywood with the force of a tsunami, and films like Bonnie and Clyde, The Graduate, Guess Who's Coming to Dinner, In the Heat of the Night, and box-office bomb Doctor Doolittle signaled a change in Hollywood-and America. And as an entire industry changed and struggled, careers were suddenly made and ruined, studios grew and crumbled, and the landscape of filmmaking was altered beyond all recognition.